ON THE ISSUE OF RESTRUCTURING THE SYSTEM OF ADMINISTRATIVE LAW: SEPARATE SCIENTIFIC PROPOSALS - Ryabchenko, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the purpose of the scientific article is to reveal the main problems of restructuring the system of administrative law, updating scientific views on the subject of administrative law. Methods: to achieve this goal were used general and special scientific (special) methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization, etc. Results: when substantiating the subject of administrative procedural law should take into account its regulatory basis, which drafts the procedural code - the Code of Administrative Procedure of Ukraine. It is inexpedient to combine judicial administrative proceedings and proceedings in cases of administrative offenses in the structure of administrative procedural law. Discussion: the inexpediency at this time of changing the place of proceedings in cases of administrative offenses in the structure of the system of administrative law and noted the urgent need to update the Code of Ukraine on Administrative Offenses. The modern doctrine of administrative law requires further development of the conceptual and categorical apparatus, which should adequately denote the essence and content of new phenomena occurring in society. These are such key categories as «administrative procedural law», «administrative jurisdiction», «procedural form». The existence of judicial control over legality in public law relations in the procedural form of judicial administrative jurisdiction actualizes the scientific discussion on the separation of administrative procedural law and a clear definition of its subject. At the same time, the existing approach to belonging to the administrative process in essence, extra-procedural activities - consideration of appeals (including complaints of citizens), disciplinary proceedings, numerous non-jurisdictional proceedings - requires revision from the standpoint of their stages based on the application of stage autonomy. their designation of the category «administrative procedure». Forming a scientific approach to revising the structure of the system of administrative law, it is advisable to propose the allocation of material, procedural and procedural components. When substantiating the subject of administrative procedural law, one should take into account the existence of its normative basis, which is the procedural code - the Code of Administrative Procedure of Ukraine. The combination in the structure of administrative procedural law of judicial administrative proceedings and proceedings in cases of administrative offenses is impractical, given: a) different purpose; b) different subject; c) differences in principles and procedures. With regard to administrative proceedings, consideration of its place in the structure of the administrative law system is currently not appropriate, but there is an urgent need to update the Code of Administrative Offenses of Ukraine, which was adopted in 1984 and which has been amended. in order to update its instructions, without changing the procedural basis.